The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/hipo.23534
|View full text |Cite
|
Sign up to set email alerts
|

View cells in the hippocampus and prefrontal cortex of macaques during virtual navigation

Abstract: Cells selectively activated by a particular view of an environment have been found in the primate hippocampus (HPC). Whether view cells are present in other brain areas, and how view selectivity interacts with other variables such as object features and place remain unclear. Here, we explore these issues by recording the responses of neurons in the HPC and the lateral prefrontal cortex (LPFC) of rhesus macaques performing a task in which they learn new context‐object associations while navigating a virtual env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(57 reference statements)
1
13
1
Order By: Relevance
“…10. Several papers (including several in this Special Issue) have highlighted the presence of hippocampal and related neurons in primates including humans that respond to views of scenes, and not to the place where the individual is located (Corrigan et al, 2023;Donoghue et al, 2023;Mao et al, 2021;Tan et al, 2021;Tsitsiklis et al, 2020;Yang et al, 2023;Zhu et al, 2023). This helps to establish the encoding of views as key to understanding hippocampal function in primates including humans (Rolls, 2023b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10. Several papers (including several in this Special Issue) have highlighted the presence of hippocampal and related neurons in primates including humans that respond to views of scenes, and not to the place where the individual is located (Corrigan et al, 2023;Donoghue et al, 2023;Mao et al, 2021;Tan et al, 2021;Tsitsiklis et al, 2020;Yang et al, 2023;Zhu et al, 2023). This helps to establish the encoding of views as key to understanding hippocampal function in primates including humans (Rolls, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Several contributions to the Special Issue of Hippocampus (2023) provide evidence that many primate hippocampal neurons respond to the location being viewed "out there," not the place where the individual is located (Corrigan et al, 2023;Rolls, 2023b;Wirth, 2023;Zhu et al, 2023). Complementary evidence is also available for humans, in that in another paper in this Special Issue of Hippocampus, it was found that significant numbers of spatial view cells but not a significant number of place cells were found in the medial temporal lobe in a VR navigation task to the remembered location in a scene of a Treasure Chest (Donoghue et al, 2023).…”
Section: View Cell Spatial Coordinates: Allocentric Versus Facing Dir...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, several studies have continued the quest of understanding allocentric versus egocentric representation in the hippocampus and surrounding areas. In a study of monkeys performing a context-object association task in a virtual environment, a considerable number of view cells were found in the hippocampus that activated whenever the monkey viewed a left or right side corridor at either end of a central corridor, thus potentially representing particular views in an egocentric rather than an allocentric coordinate framework (Corrigan et al, 2023). In another study, egocentric tuning was found in deep layers of the lateral entorhinal cortex in rats (C. Wang et al, 2023), extending previous work demonstrating egocentric tuning in the superficial layers of the lateral entorhinal cortex (C. Wang et al, 2018) and in the retrosplenial cortex (Alexander et al, 2020).…”
Section: Example 2: Comparing Allocentric and Egocentric Reference Fr...mentioning
confidence: 99%
“…However, I propose that the main difference between rodents and primates lies in the way that visual stimuli are encoded in the hippocampus, with primate hippocampal encoding preserving some egocentric codes beyond retinotopic or head/body centered reference frames in visual and parietal cortices. Taking into account the persistence of egocentric signals referencing stimuli with respect to the self in the primate hippocampal complex (Corrigan et al, 2023;Yang et al, 2023), it appears that primates' hippocampal cells privilege a first person' viewer perspective which maintains some egocentric attributes rather than an allocentric perspective. Items can be represented in relationship with others, but this allocentric relationship stays anchored to the first person's perspective limited to the front facing FOV characteristic of primates.…”
mentioning
confidence: 99%